Analisa Geokimia Fluida Manifestasi Permukaan di Daerah Panas Bumi Lahendong - Jeferson Polii; Alfrie Musa Rampengan (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
Geothermal energy depends on volcanic regions or plate subduction. Indonesia has geothermal potential due to the meeting of 3 (three) large plates. North Sulawesi is one of the areas located in the ring of fire. Some areas in the Minahasa Regency, North Sulawesi province, were targeted for research because they have manifestations of geothermal such as hot pools, steaming ground, mud pools, and other manifestations. The research location is divided into 3 (three) locations around the Lahendong geothermal area, namely the Lahendong pine forest, the Toraget hot air area, and the hot springs in the village of Totolan. The results of sample and ploting tests in ternary diagrams show that all three geothermal manifestations have sulfuric acid type fluids. This type of geothermal fluid has a high SO4 content, while HCO3 and Cl values ​​are low. Hot springs that have a type of sulfuric acid occur in active volcanic regions. This is supported by the lithology of three areas of manifestation which are composed of basalt resulting from volcanic rocks.